Integrated Analysis of Long Non-coding RNAs (LncRNAs) and mRNA Expression Profiles Reveals the Potential Role of LncRNAs in Skeletal Muscle Development of the Chicken - Li, Zhenhui; Ouyang, Hongjia; Zheng, Ming; Cai, Bolin; Han, Peigong; Abdalla, Bahareldin A.; Nie, Qinghua; Zhang, Xiquan (Frontiers in Physiology, 2017)
Long non-coding RNAs (lncRNAs) play important roles in transcriptional and post-transcriptional regulation. However, little is currently known about the mechanisms by which they regulate skeletal muscle development in the chicken. In this study, we used RNA sequencing to profile the leg muscle transcriptome (lncRNA and mRNA) at three stages of skeletal muscle development in the chicken: embryonic day 11 (E11), embryonic day 16 (E16), and one day after hatching (D1). In total, 129, 132, and 45 differentially expressed lncRNAs, and 1798, 3072, and 1211 differentially expressed mRNAs were identified in comparisons of E11 vs. E16, E11 vs. D1, and E16 vs. D1, respectively. Moreover, we identified the cis- and trans-regulatory target genes of differentially expressed lncRNAs, and constructed lncRNA-gene interaction networks. In total, 126 and 200 cis-targets, and two and three trans-targets were involved in lncRNA-gene interaction networks that were constructed based on the E11 vs. E16, and E11 vs. D1 comparisons, respectively. The comparison of the E16 vs. D1 lncRNA-gene network comprised 25 cis-targets. We determined that lncRNA target genes are potentially involved in cellular development, and cellular growth and proliferation using Ingenuity Pathway Analysis. The gene networks identified for the E11 vs. D1 comparison were involved in embryonic development, organismal development and tissue development. The present study provides an RNA sequencing based evaluation of lncRNA function during skeletal muscle development in the chicken. Comprehensive analysis facilitated the identification of lncRNAs and target genes that might contribute to the regulation of different stages of skeletal muscle development.